AB065. MDM2 SNP309 polymorphism and lung cancer risk - Chi, Tran Khanh (Ann Transl Med, 2015)
Lung cancer is the most common type of cancer with high incidence rate and leading cancer cause death worldwide. Murine double minute 2 (MDM2) SNP309 polymorphisms have been reported to influence the risk of lung cancer. This study was conducted to determine the associate of the MDM2 SNP309 polymorphisms and lung cancer risk. One hundred and fifty patients were diagnosed with lung cancer in Respiratory Center, Nuclear Medicine and Oncology Center-BachMai Hospital and 173 controls who were selected to analyze clinical features and MDM2-SNP309 associated with lung cancer risk. The 309 GG genotype was associated with increased lung cancer risk in recessive model (OR =1.82; 95% CI, 1.09-3.05; P=0.02).